The Relationship Between Self-Regulated Learning and Academic Achievement on the College Students of Universitas Muhammadiyah Sidoarjo, Indonesia - Ika Wulan Ramadhani; Nurfi Laili (Indonesian Journal of Islamic Studies, 2021)
This study aims to determine the relationship between self-regulated learning and academic achievement of students of the Madrasah Ibtidaiyah Teacher Education Study Program, Faculty of Islamic Religion, University of Muhammadiyah Sidoarjo. The type of research used in this study is a quantitative method with a correlational approach. The variables in this study are self-regulated learning as the independent variable and academic achievement as the dependent variable. The population in this study were 108 students. The author uses the method of issac and michael with a level of 5% so that the total population that is used as a sample according to the issac and michael table is 84 students. The sampling technique used is stratified random sampling. Data collection uses a Likert model scale, namely the self-regulated learning scale. And use the cumulative grade point average or GPA to see student academic achievement. Analysis of the research data using correlation techniques using SPSS 25 for windows. The analysis in this study obtained a correlation coefficient of rxy = 0.376 which has a significance value of 0.000, which means that there is a positive relationship between self-regulated learning and academic achievement. It can be concluded that the higher the self-regulated learning, the higher the academic achievement of the students of the Madrasah Ibtidaiyah Teacher Education Study Program, the Faculty of Islamic Religion, University of Muhammadiyah Sidoarjo, with an effect magnitude of 42.7%. Keywords: Self regulated learning, Academic Achievement, Students, PGMI